Bootstrap 5 course : build responsive websites like a pro. (Manning Publications, 2022)
Are you interested in pursuing a rewarding career as a web developer? Or perhaps you're already building web sites and want to brush up on your skills and take things to a whole new level? There is no doubt that the future belongs to web developers who know how to build real-world responsive websites built on the Bootstrap framework. That is why we prepared the course specifically for beginners and intermediate-level students. The best way to secure a long-term career in the sector is to learn what you need to know in a hands-on manner. And that is what you'll do in this course. Bootstrap 5 is the most recent version of the world's most popular front-end frameworks. Millions of websites are built with Bootstrap, which was deliberately created to cover a broad range of conventional user interfaces. There are several benefits to building a website with Bootstrap 5, including a clean and modern style that works on any device and all browsers and screen sizes. The course starts with layouts and typography, then shows you how to work with forms and add components such as buttons and breadcrumbs. Then we'll put all the pieces together and show you how to create a responsive website start to finish, step by step, with a fun mini-project. The source code for the project is provided. You can count on finding everything you need to get up and running with coding quickly.